Cadaveric study of movement in the unstable upper cervical spine during emergency management: tracheal intubation and cervical spine immobilisation - a study protocol for a prospective randomised crossover trial - Liao, Shiyao; Popp, Erik; Weilbacher, Frank; Münzberg, Matthias; Schneider, Niko; Kreinest, Michael (BMJ open, 2017)
Introduction: Emergency management of upper cervical spine injuries often requires cervical spine immobilisation and some critical patients also require airway management. The movement of cervical spine created by tracheal intubation and cervical spine immobilisation can potentially exacerbate cervical spinal cord injury. However, the evidence that previous studies have provided remains unclear, due to lack of a direct measurement technique for dural sac9s space during dynamic processes. Our study will use myelography method and a wireless human motion tracker to characterise and compare the change of dural sac9s space during tracheal intubations and cervical spine immobilisation in the presence of unstable upper cervical spine injury such as atlanto-occipital dislocation or type II odontoid fracture. Methods and analysis: Perform laryngoscopy and intubation, video laryngoscope intubation, laryngeal tube insertion, fiberoptic intubation and cervical collar application on cadaveric models of unstable upper cervical spine injury such as atlanto-occipital dislocation or type II odontoid fracture. The change of dural sac9s space and the motion of unstable cervical segment are recorded by video fluoroscopy with previously performing myelography, which enables us to directly measure dural sac9s space. Simultaneously, the whole cervical spine motion is recorded at a wireless human motion tracker. The maximum dural sac compression and the maximum angulation and distraction of the injured segment are measured by reviewing fluoroscopic and myelography images. Ethics and dissemination: This study protocol has been approved by the Ethics Committee of the State Medical Association Rhineland-Palatinate, Mainz, Germany. The results will be published in relevant emergency journals and presented at relevant conferences. Trial registration number: DRKS00010499
Gesehen am 18.09.2018